The “montado”: determinant factor affecting the carcass characteristics and the quality of dry cured hams of Alentejano pig - Freitas, A.B. (2014)
The objective of this study was to assess the effect of the finishing system (under montanheira or with commercial feed) on carcass characteristics and dry cured-ham of Alentejano pigs. 24 pigs were fattening until 130 kg LW under montanheira and 24 pigs were fattening with commercial feed. Carcasses of pigs fattened under the montanheira system were slightly heavy (98,38 vs 96,13 kg), with significantly higher (P>0,01) dressing percentage (79,55% vs 78,11%), backfat thickness (6,09 vs 5,34 cm), percentage of fatty cuts (32,06% vs 30,44%) and weight (21,92 vs 19,77 kg) and percentage of adipose tissue (51,65% vs 47,71%). Percentage of lean cuts (50,03% vs 49,07%), bone cuts (19,53% vs 18,87%), weight (14,91 vs 13,77 kg) and percentage of lean (36,04% vs 32,54%), lean:bone (3,21 vs 3,01) and lean:fat (0,76 vs 0,63) ratios were significantly higher in pigs fed commercial feed. The content of ether extract in lean+fat was significantly higher (63,7% vs 60,41%), in pigs fattened under the montanheira system, while the content of crude protein (7,57% vs 8,41%) was significantly higher in pigs fed commercial feed. Energy retained was higher in pigs finished under montanheira (231,7 vs 217,0 Mcal). The dry cured hams from pigs fattened on acorns were more mono-unsaturated and less poly-unsaturated, especially on subcutaneous fat. It can be concluded that the fattening on pasture and acorns under the oak canopy is considered to be crucial for the quality of the raw material and meat products, as dry cured-ham.